Tipping points : : are we tipping our earth into a hothouse state? - Rehn, Lisa (2021)
Abstract: Tipping points are critical points at which sub-systems of our planet are drastically altered by small disruptions. Tipping a system leads to irreversible responses which can push the Earth into a Hothouse state. Past the tipping point, self-reinforcing feedbacks within the system instead of human influences will become the main drivers of change. Additionally, so-called domino effects will amplify changes as tipping of one system leads to tipping of others. Although it might be too late for some systems, it is imperative that the Paris Climate Agreement goals are reached in order to prevent the drastic and unforeseeable changes that result from tipping our Earth’s systems